Where's the Omelet? Bad King Deng and the Challenges of Biography and History. Issue 1 (11th January 2016) - Hayford, Charles W.
Abstract : Stalinists legitimized their methods by saying "you can't make omelets without breaking eggs." Others might ask, "you broke lots of eggs, but where are the omelets?" These three biographies of Deng Xiaoping are only the most recent of biographies of epoch-making Chinese leaders that assess the ratio of broken eggs to finished omelets. Reading them together with the body of reviews provokes questions about how biography as a genre can usefully address historical analysis and moral judgment. How much could a single leader transform China? Did Deng merely inherit institutions and decisive policies from earlier leaders or is China today somehow "Deng's China"? What can we learn about the problems from reviewers and critics?